Evaluation of the association between obesity and global DNA methylation - Mahjoob, Zahraa A. M; Lafta, Fadhel Mohammed; Ashor, Ammar W. (Iraqi Journal of Science, 2025)
Obesity has become a global epidemic at an increasing rate with the potential to be influenced by epigenetic alterations, including DNA methylation. Considering the lack of local studies investigating the influence of global DNA methylation alterations on obesity, the present study was set out to address this issue.A total of 90 subjects were involved in the present study. Sixty participants were obese (BMI > 30 kg/m2) while 30 participants were normal body weight (BMI < 25 kg/m2). The average age was 31.5 years with a range of (20 – 50 years). Following DNA extraction, global DNA methylation levels were assessed using MethylFlash™ Global DNA Methylation (5mC) ELISA Easy Kit. Other obesity related bio-parameters (including insulin, fasting blood sugar (FBS), insulin resistance, lipid profile, liver enzymes, and total antioxidant capacity(T-AOC) were also compared between obese and non-obese subjects.The levels of global DNA methylation (5mC%) were significantly (P˂0.0001) reduced in the investigated obese versus normal weight controls (0.348 ±0.01 vs.0.559 ±0.02). In addition to the significantly elevated levels ((P≤0.001) T-AOC in the obese subjects in comparison to normal weight controls (0.191 ±0.01vs. 0.132 ±0.01). Lipid profile parameters analysis showed significantly elevated (P≤0.01) cholesterol and LDL in the obese subjects than their normal weight counterparts (191.65 ±3.95 vs. 109.40 ±7.59, and 129.25 ±5.20 vs. 75.93 ±3.22, respectively). The present study showed that the reduced global DNA methylation level is negatively correlated with body mass index of the investigated subjects (r = - 0.441, p˂0.0001). The present study finding may support the involvement of DNA methylation alteration in the obesity pathogenesis.